2017
DOI: 10.3892/ol.2017.6544
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of estrogen receptor β in androgen receptor-induced growth inhibition in prostate cancer PC-3 cells

Abstract: Previous studies have suggested that changes in sex hormone receptor expression may be associated with the initiation and progression of prostate cancer (PCa). Therefore, the present study aimed to investigate the association and possible pathways between two sex hormone receptors and PCa by measuring the expression levels of the androgen receptor (AR) and the estrogen receptor subtypes alpha (ERα) and beta (ERβ) in prostatic cancer PC-3 cell lines. The pcDNA3.1-hERβ plasmid was transfected into PC-3 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…ERβ is a specific estrogen receptor that acts as a tumor suppressor in diverse cancers, including colon cancer, breast cancer, ovarian cancer, and prostate cancer 6–9. A previous study has proved that the expression of ERβ is significantly lower in GC tissues than in normal tissues 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERβ is a specific estrogen receptor that acts as a tumor suppressor in diverse cancers, including colon cancer, breast cancer, ovarian cancer, and prostate cancer 6–9. A previous study has proved that the expression of ERβ is significantly lower in GC tissues than in normal tissues 14.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor beta (ERβ) is a hormone-inducible transcription factor that downregulated in diverse cancers, such as colon cancer,6 breast cancer,7 ovarian cancer,8 and prostate cancer 9. A large number of previous studies have proved that ERβ plays a key regulatory role in the occurrence and development of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen signaling is critical in prostate cancer, but the mechanism is poorly understood, and ERβ may play an important function in the AR signaling pathway. Recent investigations have shown that androgen-activated androgen receptors can interact not only directly through binding to estrogen response elements, but also indirectly with SP-1 (specificity protein-1), AF-1 (activation protein-1), and nuclear factor κB proteins by binding to the corresponding ligands and regulating AR signaling at the transcriptional or post-transcriptional level, which in turn affects prostate cancer progression [ 32 35 ]. Researchers found elevated epithelial hyperplasia and AR downstream genes level in a ERβ knockout mouse model, most of which were also upregulated in prostate cancer, prompting consideration of whether crosstalk exists between these 2 signaling pathways [ 36 ].…”
Section: The Regulatory Effect Of Erβ On Ar Signal In Prostate Cancermentioning
confidence: 99%